Patient expectations and perceived social support related to return to sport after anterior cruciate ligament reconstruction in adolescent athletes. (January 2021) - Armento, Aubrey; Albright, Jay; Gagliardi, Alexia; Daoud, Ariel Kiyomi; Howell, David; Mayer, Stephanie
Abstract: Objective: Examine the relationship between pre-operative competitive status and return to sport expectations post-operatively among adolescents undergoing ACL reconstruction. Assess the association between perceived levels of social support and doubts in returning to sport after ACL reconstruction. Design: Cross-sectional. Setting: Outpatient sports medicine clinic at a single institution. Participants: 12–18 years old with an ACL tear who were planning to undergo ACL reconstruction. Main outcome measures: Psychovitality questionnaire responses and Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire scores. Results: 86% of participants expected to return to sports in six months or less after surgery; there was no significant difference in expected time to return to sport between competitive vs. recreational athletes. Competitive athletes were less likely to be content returning to a lower activity level after surgery compared to recreational athletes. There were no significant differences in MSPSS scores between those who did and did not report doubts in their ability to return to their previous sports. Conclusion: Most of our adolescent athlete population expected to return to sport after ACL reconstruction within six months of surgery. Those with and without doubts in their ability to return to sports did not significantly differ in levels of perceived social support. Highlights: Evidence suggests psychological factors contribute to a patient's successful return to sport after ACL reconstruction. Many adolescent athletes expected to return to sport after ACL reconstruction far sooner than the expected timeline. An athlete's competition status prior to ACL reconstruction may lead to heightened expectations of returning to sport. Our data did not demonstrate a significant relationship between psychosocial support and doubts in returning to sport.